Cyclophosphamide Treatment Mimics Sub-Lethal Infections With Encephalitozoon intestinalis in Immunocompromised Individuals - Moura, Maria Lucia Costa de; Alvares-Saraiva, Anuska Marcelino; Pérez, Elizabeth Cristina; Xavier, José Guilherme; Spadacci-Morena, Diva Denelle; Moysés, Carla Renata Serantoni; Rocha, Paulo Ricardo Dell’Armelina; Lallo, Maria Anete (Frontiers in Microbiology, 2019)
Microsporidia, including Encephalitozoon intestinalis, are emerging pathogens which cause opportunistic infections in immunocompromised patients, such as those with AIDS, cancer, the elderly and people on immunosuppressive drugs. Intestinal mucosa (IM) is crucial for developing an efficient adaptive immune response against pathogenic micro-organisms, thereby preventing their colonization and subsequent infection. As immunosuppressive drugs affect the intestinal immune response is little known. In the present study, we investigated the immune response to E. intestinalis infection in the IM and gut-associated lymphoid tissue (GALT) in cyclophosphamide (Cy) immunosuppressed mice, to mimic an immunocompromised condition. Histopathology revealed lymphoplasmacytic enteritis at 7 and 14 days-post-infection (dpi) in all infected groups; however, inflammation diminished at 21 and 28 dpi. Cy treatment also led to a higher number of E. intestinalis spores and lesions, which reduced at 28 dpi. In addition, flow cytometry analysis demonstrated CD4+ and CD8+ T cells to be predominant immune cells, with up-regulation in both Th1 and Th2 cytokines at 7 and 14 dpi, as demonstrated by histopathology. In conclusion, Cy treatment reduced GALT (Peyer's plaques and mesenteric lymph nodes) and peritoneum populations but increased the T-cell population in the intestinal mucosa and the production of pro-and anti-inflammatory cytokines, which were able to eliminate this opportunistic fungus and reduced the E. intestinalis infection.